Critical evaluation of the theory of justice of John Rawls - Aranda Fraga, Fernando (2013)
Under the strong influence of the dominant Kantian legacy in much of the twentieth century ethics, Rawls designs a theory of justice whose highest aspiration is to be impartial, whereby theory attempts to refute the two dominant ethical currents in his time : utilitarianism and intuitionism. The neocontractualism of John Rawls arises in the spectrum of contemporary political philosophy as a broad-based liberalism, whose main purpose is to provide a pluralistic framework, capable of regulating the delivery of justice in a well ordered society. In Rawls, the priority of the right over the good would be signaling a willingness to take a choice of ethics and justice and concurrent broad but lacking in substantive moral theory, in the spirit of an era devoid of anthropological content able to properly explain human and social reality.